Trophic, Chemo-Ecological and Sex-Specific Insights on the Relation Between Diplodus sargus (Linnaeus, 1758) and the Invasive Caulerpa cylindracea (Sonder, 1845) - Miccoli, Andrea; Mancini, Emanuele; Boschi, Marco; Provenza, Francesca; Lelli, Veronica; Tiralongo, Francesco; Renzi, Monia; Terlizzi, Antonio; Bonamano, Simone; Marcelli, Marco (Frontiers in Marine Science, 2021)
Biological invasions result in negative and unpredictable impacts on oceans worldwide. Non-indigenous macrophytes often synthesize secondary metabolites for defensive purposes and increased competition efficiency: this is the case of Caulerpa cylindracea, which has entered the Mediterranean Sea in 1990 and competed against local flora and fauna since. It was demonstrated that the white seabream Diplodus sargus (i) has included the algae into its diet, (ii) is subject to the peculiar Abnormally Tough Specimen (ATS) condition post-cooking, and (iii) suffers physiological and behavioral disturbances from caulerpin, one of the three major algal secondary metabolites. This paper confirms a feeding relationship between the fish and the algae, quantifies caulerpin accumulation in the liver, suggests a possible mollusk- and echinoderm-driven biomagnification, and highlights the fact that all ATS specimens were males. Multivariate analyses on a multi-biomarker panel reveals differential correlations to key cellular processes such as oxidative stress, metabolism, neurotoxicity, and lipid peroxidation as well as to condition indexes.